Mandatory Minimum Sentences of Imprisonment: Exploring the Consequences for the Sentencing Process - Roberts, Julian V. (2001)
In this article, the author discusses the nature and consequences of the mandatory sentences of imprisonment created by Bill C-63 in 1995. These mandatory sentences constitute the most comprehensive collection of mandatory minima in Canadian history, and will affect significant numbers of offenders. Unlike most mandatory minima created in other jurisdictions such as Australia, England, and Wales, the legislation that created the firearms offence minima offer no provision to be invoked in exceptional cases. In this article, the author addresses the effect that these new statutory minima am likely to have on sentencing patterns It is argued that they should not have an inflationary effect on sentence lengths for all firearms offences, and certainly not for other, unrelated crimes. Allowing the new mandatory minima to inflate sentencing lengths would cause considerable damage to the architecture of the sentencing system. Such a change would also be inconsistent with the codified principles of sentencing. The article concludes by reiterating a proposal to promote a more rational and coherent sentencing policy development: creation of a Permanent Sentencing Commission